POLITIK LUAR NEGERI KOREA SELATAN TERHADAP REPUBLIK RAKYAT CHINA (RRC) PADA MASA PEMERINTAHAN PARK GEUN-HYE DALAM MEMBENTUK REZIM KEAMANAN DI SEMENANJUNG KOREA - Dyan Maulidha Nugraheny (HI 16 UMY 164, 2016)
*164 Korean Peninsula crisis has been occuring since 1950s. Until now, the crisis of the two Koreas keep going as the North keeps doing any efforts that leads to escalate the conflict. The new Park Geun-hye governance in 2013 was welcomed by the North Korea’s 3rd nuclear test which every nation condemned at. Therefore, with every considerations, South Korean government need to seek for new alliance to protect its national security from the threats and China, which has been North Korea’s old alliance as well as The North’s source of external power, is probably the best choice for Park’s government.